Determinan Perilaku Hidup Bersih dan Sehat (PHBS) pada Ibu Rumah Tangga di Wilayah Desa Tumbang Masukih Kabupaten Gunung Mas Provinsi Kalimantan Tengah - Kurniawan, Aprizal; Rupiwardani, Irfany; Cahyani, Septia Dwi (Jurnal Sanitasi Profesional Indonesia, 2025)
Clean and healthy living practices in Indonesia are currently still low, which is related to various environmental health issues that are still high in Indonesia. In rural areas, especially in Tumbang Masukih Village, public awareness of the importance of practicing clean and healthy living is still minimal. Geographically, Tumbang Masukih Village is located in a highland area adjacent to a major river, with water from this river supporting daily water needs such as cooking, washing, and other activities. Therefore, community knowledge about the implementation of PHBS is of great importance. The objective of this study is to analyze the determinants of clean and healthy living behavior (PHBS) among housewives in the Tumbang Masukih Village area of Gunung Mas District, Central Kalimantan Province.The research method used was quantitative research with a cross-sectional approach. The research population consisted of 107 housewives who did not work in Tumbang Masukih Village, with a sample of 52 housewives selected using random sampling. The research instrument used a questionnaire with chi-square statistical data analysis.The results showed a relationship between the independent and dependent variables. This is evidenced by the p-value of each variable being < α (0.05), indicating a significant and meaningful relationship between education, attitude, knowledge, and social support toward clean and healthy living behavior. The conclusion from this study is that there are determinants of clean and healthy living behavior (PHBS) among housewives in the Tumbang Masukih Village area of Gunung Mas District, Central Kalimantan Province.